Objectives and Methods of Analyzing Energy Efficiency in the Economy - Chaika Larisa V. (Economic and Social Changes: Facts, Trends, Forecast, 2018)
Energy saving and improving energy efficiency of production are among economic development priorities in Russia and its regions. Energy efficiency issues are given a lot of attention in scientific research on the interrelation of economic and power engineering development. In order to select the methodological tools for regional studies, we have reviewed scientific publications that analyze and evaluate energy efficiency in the economy. As a result of the review, we highlight the relevant research objectives: 1) to clarify the trends and factors leading to changes in energy efficiency of the objects under consideration; 2) to compare the energy efficiency of similar objects, to determine the causes of differences and possible growth potential; 3) to identify the spatiotemporal properties of energy variables and causal relationships between energy consumption and economic growth. In accordance with these research objectives we summarize the approaches and methods of statistical analysis, evaluation, and econometric modeling used to address them. The practical results of the studies carried out for different countries in different time periods are ambiguous. For the most part, the analytical tools used require a detailed statistical database of energy and economic indicators and special software. Not all of the tasks highlighted in this review are equally relevant in regional studies. In the light of the implementation of energy-saving policy in Russia, we consider the following issues to be of top priority: analyzing energy and economic trends in regional development and the factors that have the greatest impact on their formation, using the methods of decomposition, regression and boundary analysis. Interregional comparison with the use of the cluster and boundary analysis is used to clarify the pattern of spatial differentiation of energy efficiency and trends in its temporary transformation. The problems of complex econometric modeling of the regional economy with the detailed description of the dependence of energy variables deserve the greatest attention since they can help create a unified system of monitoring, analyzing and forecasting the key indicators of development in each region of Russia